A 3D printed Ga containing scaffold with both anti-infection and bone homeostasis-regulating properties for the treatment of infected bone defects. Issue 23 (6th June 2021) - Wang, Minqi; Yang, Yiqi; Chi, Guanghao; Yuan, Kai; Zhou, Feng; Dong, Liang; Liu, Haibei; Zhou, Qinghui; Gong, Weihua; Yang, Shengbing; Tang, Tingting
Abstract : A dual-functional 3D printed scaffold with both anti-infection and bone homeostasis-regulating properties for infected bone defect treatment. Abstract : Large bone defects face a high risk of infection, which can also lead to bone homeostasis disorders. This seriously hinders the bone healing process; therefore, the help of a dual-functional scaffold that has both anti-infection and bone-homeostasis-regulating capacities is needed in the treatment of infected bone defects. In this study, a 3D printed dual-functional scaffold composed of poly-ε-caprolactone (PCL), mesoporous bioactive glasses (MBG), and gallium (Ga) was produced. In vitro experiments demonstrated the excellent antibacterial ability of the PCL/MBG/Ga scaffold against methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli ( E. coli ). The scaffold also significantly inhibited osteoclastic activity and promoted osteogenic differentiation. Furthermore, a rabbit model with an infected bone defect in the radius was used to evaluate the in vivo bone healing capability of PCL/MBG/Ga. The results demonstrate that the PCL/MBG/Ga scaffold can significantly accelerate bone healing and prevent bone resorption, suggesting its potential for application in repairing infected bone defects.